The Efficiency of Educational Intervention Based on PRECEDE Educational Method in the Promotion of Life Quality of the Aged Under the Coverage of Tehran Cultural House of Aged People 2009 - Mohammad Eshak Afkari (Sālmand, 2011)
Objectives: The aim of this study was to investigate the efficiency of educational Abstract  intervention based on PRECEDE educational method in the promotion of quality of life among the aged under the coverage of Tehran Cultural House of Aged People 2009. The population of the aged [people] is increasing in all parts of the world even in developing countries. The increase of the number of the aged has created an international trend to increase the quality of life for them. The purpose of performing this project is to study the impact of educational interference based on PRECEDE model in promoting the quality of life of the aged.